Design Of Dual-Band Microstrip Patch Antenna With Right-Angle Triangular Aperture Slot For Energy Transfer Application - Hassan, Nornikman; Zakaria, Zahriladha; Sam, Weng Yik; Mohd Hanapiah, Izyan Nazihah; Mohamad, A.Nasoruddin; Roslan, Ameer Farhan; Ahmad, Badrul Hisham; Ismail, Mohd Khairy; Abd. Aziz, Mohamad Zoinol Abidin (John Wiley & Sons Inc., 2019)
This work focusing on the dual‐band antenna design with rectifying circuit for energy transfer system technology for enhancement gain performance. The air gap technique is applied on this microstrip antenna design work to enhance the antenna gain. The work begins with designing and analyzing the antenna via the CST Microwave Studio software. After validation on acceptable performance in simulation side is obtained, the return loss, S11 of the antenna is measured using vector network analyzer equipment. The rectifier circuit is used to convert the captured signal to DC voltage. This projected dual‐band antenna has successfully accomplished the target on return loss of −44.707 dB and −32.163 dB at dual resonant frequencies for 1.8 GHz and 2.4 GHz, respectively. This proposed antenna design benefits in low cost fabrication and has achieved high gain of 6.31 dBi and 7.82 dBi for dual‐band functioning frequencies.